The psy-disciplines go to school: psychiatric, psychological and psychotherapeutic approaches to inclusion in one UK primary school. Issue 6 (3rd June 2018) - Barker, Beth; Mills, China
ABSTRACT: A growing body of research, largely from the global North, and particularly from North America, highlights the increasing psychiatrisation, medicalisation and psychologisation of children and childhood, and suggests that schools and educators play a key role in these processes. This increasing diffusion of psy-expertise within educational spaces signifies a cultural shift that has profound effects on teacher and student subjectivity, and on institutional and professional practices. Educators in many countries are said to be on the 'front-line' in identifying mental health issues, recommending treatment pathways, and sometimes helping to administer psychopharmaceuticals. The alacrity with which educators engage in these practices varies internationally, with reported occurrence being much higher in the United States and Canada, compared to the United Kingdom, where there is a lack of research. Drawing upon a case study in a UK primary school, this paper makes an original and timely contribution to research into UK teacher's perceptions of inclusion in relation to social, emotional and behavioural difficulties and, in particular, attention-deficit hyperactivity disorder, as they navigate the interface of psychology and education. Contrary to some previous research, the educators in this study viewed the distribution of psychopharmaceuticals negatively, and showed a preference for psychotherapeutic approaches to inclusion. This research provides much needed empirical findings to a growing but largely theoretically informed body of research exploring whether, and if so then how, educators are implicated in the mobilisation of psy-expertise within children's lives.